1997
DOI: 10.1111/j.1095-8649.1997.tb02000.x
|View full text |Cite
|
Sign up to set email alerts
|

Tilapia are able to withstand long‐term exposure to low environmental pH, judged by their energy status, ionic balance and plasma cortisol

Abstract: Tilapia Oraochromis mossambicus were exposed to water at pH 4-0 for 37 days. The water was acidified slowly over 6 h enabling the animals to acclimate and preventing damage of the gill epithelium. Additional stressors, e.g. aluminium ions and handling stress, were avoided. No mortality or decreased food consumption was observed during the exposure period. No significant changes were observed between the control and acid exposed groups for the energy rich compounds and related parameters, i.e. Lhe adenylate ene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0
2

Year Published

2001
2001
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 42 publications
1
6
0
2
Order By: Relevance
“…Plasma pH values between 7.3 and 7.5 have been reported to be normal values in fish (Hirata et al, 2003), which correspond well with the values found in our study. A two-day decrease of water pH was not experienced as stressful in the present study as indicated by the lack of a significant rise in plasma pH and cortisol levels, which is in line with previous reports (Ginneken et al, 1997;Lamers et al, 1994), in which either a 6h or a 24h period of gradual water acidification was applied. However, plasma pH levels were generally lower when water acidification (water pH at 4.5) was applied after 25 days of undisturbed adaptation, indicating a reduced capacity to maintain plasma pH levels.…”
Section: Plasma Analysis -Effects O F Water Acidificationsupporting
confidence: 78%
See 1 more Smart Citation
“…Plasma pH values between 7.3 and 7.5 have been reported to be normal values in fish (Hirata et al, 2003), which correspond well with the values found in our study. A two-day decrease of water pH was not experienced as stressful in the present study as indicated by the lack of a significant rise in plasma pH and cortisol levels, which is in line with previous reports (Ginneken et al, 1997;Lamers et al, 1994), in which either a 6h or a 24h period of gradual water acidification was applied. However, plasma pH levels were generally lower when water acidification (water pH at 4.5) was applied after 25 days of undisturbed adaptation, indicating a reduced capacity to maintain plasma pH levels.…”
Section: Plasma Analysis -Effects O F Water Acidificationsupporting
confidence: 78%
“…When fish have already adapted for 25 days to a given background, a decrease in water pH does no longer influence the pigmentation response. According to Ginneken et al (1997) and Lamers et al (1994), tilapia are able to handle a low pH quite well as long as the water pH is lowered gradually, for instance over a two-day period. The response of the tilapia in our study confirms that a twoday decrease of pH from 7.8 to 4.5 is slow enough not to disrupt hydromineral homeostasis.…”
Section: Pigmentation -Effects O F Water Acidificationmentioning
confidence: 99%
“…In the case of carp, therefore, low pH may be a stressor. In contrast, van Ginneken, van Eersel, Balm, Nieveen and van den Thillart (1997) reported that plasma concentrations of sodium, chloride, cortisol and glucose did not change in Mozambique tilapia after exposure to acidic conditions (pH 4.0) for 3, 17 and 37 days, and suggested that the ionic balance was maintained even in acidic conditions. Tilapia may have higher tolerance for low pH conditions.…”
Section: Resultsmentioning
confidence: 90%
“…However, its transcript level decreased to the normal level after 24 h, and its enzymatic activity was lower than the control group after 48 h. These facts demonstrate the inhibition of strong acidification on Cu/Zn‐SOD at the late period. It has been reported that juvenile tilapia could survive in acidic water at pH 4.0 for 37 d without any changes of food consumption, energy status, or ionic balance (van Ginneken et al ). However, the fact that strong acidic‐exposed tilapia presented a fluctuation in mRNA expression and activity of Cu/Zn‐SOD indicates antioxidant activity was affected by the strong acidic water though fish could survive in this environment.…”
Section: Discussionmentioning
confidence: 99%
“…The suitable pH for survival of larval hybrid tilapia, Oreochromis niloticus × Oreochromis aureus is 6.0–8.5 and for growth is 7.0–7.5 (Qiang et al ). Juvenile Oreochromis mossambicus could survive in an alkaline environment with pH ranging between 8.0 and 9.6 for 2 mo (Mukherjee et al ) and could acclimate to water at pH 4.0 for 37 d (van Ginneken et al ). A recent study found acidic exposure induces oxidative stress and DNA damage in tilapia ( O. niloticus ) blood cells (Mai et al ).…”
mentioning
confidence: 99%